Adult-onset Still's disease as a cutaneous marker of systemic disease - Katerina Damevska; Katlein França; Suzana Nikolovska; Filip Gucev (Elsevier BV, 2019)
Adult-onset Still's disease (AOSD) is a rare, systemic, inflammatory disorder characterized by spiking fevers, an evanescent eruption, arthritis, and multiorgan involvement. The disease has been recently classified as a polygenic autoinflammatory disorder at the "crossroads" of autoinflammatory and autoimmune diseases. The highly characteristic salmon-colored eruption is a cutaneous manifestation of a generalized inflammatory reaction and an important diagnostic criterion. In addition to the evanescent eruption, there are atypical persistent papules and plaques in many patients with AOSD. Emerging data suggest that AOSD with this typical evanescent eruption has a different clinicopathologic presentation and clinical course than AODS with atypical cutaneous manifestations. It appears that there are two subtypes of AOSD with different immunologic profiles, including (1) a systemic disease with high fever, organ involvement, and elevated levels of ferritin, and (2) a chronic disease course with arthritis as the predominant finding. These observations provide novel insight into the disease pathogenesis, suggesting that the underlying mechanisms might differ between these two forms, partially explaining the reported differences in drug response. Recent advances in the understanding of AOSD are summarized with a focus on the spectrum of cutaneous manifestations and its relationship to systemic inflammation.
Keywords: adult-onset Still's disease; skin manifestations; systemic inflammation